AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK KULIT KAYU RARU (COTYLELOBIUM SP.) - Gunawan Pasaribu; Titiek Setyawati (BRIN Publishing, 2011)
Research on natural medicinal plants has been growing due to the increasing interest to natural medicinal material that is considered safer than synthetic medicines. In North Sumatera, bark of Cotylelobium sp which is locally known as raru, bas been widely utilized by the local community. The skin bark of this species is commonly used as a mixture of